Missed Connections: Representations of Gender, (Armed) Violence and Security in Resolution 1325 - Santos, Rita (2013)
This article analyzes the limitations of the United Nations Security Council Resolution on Women, Peace and Security (1325/2000) as a product of the concepts of gender, violence and security underpinning it. Although it represents an important historical advance, recognizing the potential role of women in peacemaking processes and post-conflict agreements, and ensuring that violence against them is taken seriously both nationally and internationally, the Resolution nevertheless has a number of limitations and challenges. It is argued here that the Resolution is (only) a first step towards the recognition of the connections and possibilities of dialogue between gender, violence and security, and that it does not necessarily transform the way each concept and the connections between them are understood within the United Nations, its member states and even non-governmental organizations dedicated to gender issues, particularly women’s groups. The limits of the Resolution are questioned by analyzing contexts of armed violence other than wars or post-conflict situations that are not covered by 1325, focusing particularly on their gender dynamics.